Single-Port Laparoscopic Proximal Gastrectomy with Double Tract Reconstruction for Early Gastric Cancer: Report of a Case - Lee, Chang Min (J Gastric Cancer, 2016)
In Korea, proximal gastrectomy has recently attracted attention as a better choice of function-preserving surgery for proximal early gastric cancer than total gastrectomy. Of the various strategies to overcome reflux symptoms from remnant stomach, double tract reconstruction not only reduces the incidence of anastomosis-related complications, but is also sufficiently reproducible as a laparoscopic procedure. Catching up with the recent rise of single-port laparoscopic surgeries, we performed a pure single-port laparoscopic proximal gastrectomy with DTR. This procedure was designed by merging the function-preserving concept of proximal gastrectomy with single-port laparoscopic total gastrectomy.